THE EFFECT OF ADDITIONAL DURIAN SEED FLOUR (Durio zibethinus Murr) ON CHEMICAL COMPOSITION OF BIANG FISH (Ilisha elongata) NUGGET - Agung Saputra; Dahlia Dahlia; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aimed to determine the effect of the addition of durian seed flour on the chemical composition of biang fish (Ilisha elongate) nuggets. The research method used was experimental through processing nuggets of biang fish with the addition of durian seed flour using a non-factorial Completely Randomized Design (CRD) with 4 levels of treatment, namely N0 (0%), N1 (7.5%), N2 (10%), and N3 (12.5%). The results of the study concluded that the best treatment was N3 treatment (Durian seed flour 12.5%) with the following chemical composition values: water content 55.77%, ash content 1.91%, protein content 11.28%, fat content 0 .53%, and carbohydrate content of 15.14%.Keywords: biang fish, nuggets, durian seed flour